The utility of neuropsychological consultation in identifying medical inpatients with suspected cognitive impairment at risk for greater hospital utilization. Issue 1 (2nd January 2019) - Sieg, Erica; Mai, Quan; Mosti, Caterina; Brook, Michael
Abstract: Objective: This was a retrospective study designed to examine the relationship between inpatient neuropsychological status and future utilization costs.Methods: We completed a retrospective chart review of 280 patients admitted to a large academic medical center who were referred for bedside neuropsychological evaluation. Patients were grouped based on neuropsychological recommendation regarding level of supportive needs post-discharge (low, moderate, high). Level of support was used as a gross surrogate indicator of cognitive status in this heterogeneous sample. We also included patients who refused assessment. Outcome variables included time to readmission, number of emergency department visits, inpatient admissions, length of hospitalization, and total costs of hospitalizations, 30 days and 1 year following discharge.Results: Multivariate analysis indicated patients who refused assessment had higher inpatient service utilization (number of ED visits, number of admissions, and total cost of hospitalization) compared to those with moderate needs. Also, high needs patients had higher total cost of hospitalization at 1 year, and those with low needs used the ED more, compared to those with moderate needs.Conclusions: Our findings replicate prior studies linking refusal of neuropsychological evaluation to higher service utilization costs, and suggest a nonlinear relationship between cognitive impairment severity and future costs for medical inpatients (different groups incur different types of costs). Results preliminarily highlight the potential utility of inpatient neuropsychological assessment in identifying patients at risk for greater hospital utilization, which may allow for the development of appropriate interventions for these patients.